(untitled) (Scientific journal of the Fergana State University, 2026)
Abstract This article provides an in-depth analysis of the issue of improving energy efficiency in modern computer networks. The study examines three main approaches: Adaptive Link Rate (ALR), Traffic-aware Sleep Modes (TSM), and AI-driven Load Consolidation (AILC). Simulation results demonstrate that individual strategies can achieve energy savings of 18–35%, while their combined application can increase energy efficiency by up to 48.7%. Furthermore, the observed changes in quality of service indicators remain within acceptable limits, making these strategies highly promising for practical implementation.